Improving Students’ Speaking Ability through Small-Group Discussion - Imam Fauzi (University of Muhammadiyah Prof. DR. HAMKA, 2017)
This research aimed to investigate how small-group discussion can be implemented to improve vocational high school students’ speaking ability and to identify the role of small group discussion in improving students’ speaking skill. This research was conducted by using action research, with 35 students of the second grade participating in this research. The findings of research can be explained in three cycles. Cycle 1 revealed that there were 37.2% of the students who did well; 42.8% were good although they had weaknesses in some aspects of using statements of introduction and choosing good sentences; 20% were weak and did not understand to choose appropriate sentences for introduction. Cycle II showed that 45.7% of the participants were good either in choosing appropriate sentences and pronunciation; 54.3% were considered good although they still lacked speaking communicatively with appropriate words. Cycle III was implemented after having additional classes, small guidelines of active speaking, and intensive practices. It found that 71.4% of the participants could communicate with English basic words and better structure, and 28.6% of them were still slightly below. Findings of this study showed that small group discussion could effectively improve students’ speaking skill, engage them in the group work discussion actively, encourage them to be independent learners who can expose themselves in learning activities, make them feel more relaxed at learning, give them more opportunities to improve their speaking skills.